Copper microRNAs modulate the formation of giant feeding cells induced by the root knot nematode Meloidogyne incognita in Arabidopsis thaliana. Issue 1 (8th August 2022) - Noureddine, Yara; Mejias, Joffrey; da Rocha, Martine; Thomine, Sébastien; Quentin, Michaël; Abad, Pierre; Favery, Bruno; Jaubert‐Possamai, Stéphanie
Summary: Root‐knot nematodes (RKNs) are root endoparasites that induce the dedifferentiation of a few root cells and the reprogramming of their gene expression to generate giant hypermetabolic feeding cells. We identified two microRNA families, miR408 and miR398, as upregulated in Arabidopsis thaliana and Solanum lycopersicum roots infected by RKNs. In plants, the expression of these two conserved microRNA families is known to be activated by the SPL7 transcription factor in response to copper starvation. By combining functional approaches, we deciphered the network involving these microRNAs, their regulator and their targets. MIR408 expression was located within nematode‐induced feeding cells like its regulator SPL7 and was regulated by copper. Moreover, infection assays with mir408 and spl7 knockout mutants or lines expressing targets rendered resistant to cleavage by miR398 demonstrated the essential role of the SPL7 / MIR408 / MIR398 module in the formation of giant feeding cells. Our findings reveal how perturbation of plant copper homeostasis, via the SPL7 / MIR408 / MIR398 module, modulates the development of nematode‐induced feeding cells.